Productivity and grain quality of spring wheat depending on the growth regulator “rostok” in the northern forest-steppe of the Tyumen region - A. A. Kazak; Yu. P. Loginov; S. N. Yashchenko (Зерновое хозяйство России, 2025)
The purpose of the current study was to find out the effect of the growth regulator “Rostok” on productivity and grain quality of spring wheat varieties ‘Iren’ and ‘Ikar’ in the forest-steppe of the Tyumen region. The study was conducted from 2014 to 2017 at the experimental plot of the Northern Trans-Ural SAU, where there was studied the effect of the humic product “Rostok” on the length of interphase periods, photosynthetic activity of leaves, productivity, and grain quality of spring common wheat varieties. The work was conducted both in the field and in the laboratory. The cultivation technology of spring common wheat corresponded to the recommendations for the Tyumen region and included primary plowing to a depth of 26–28 cm, spring harrowing, fertilizing (N60P60K45) and pre-sowing cultivation to a depth of 6–7 cm. Sowing was carried out by the SSFK-10 seeder with a seeding rate of 6.2 million germ.grains per hectare. The objects of the study were two varietal registered varieties of spring common wheat ‘Iren’ (middle-early) and ‘Ikar’ (middle-ripening). The study was conducted using generally accepted methods, including the Methodology of the State Variety Testing. A. A. Nichiporovich method was used to determine the photosynthetic activity of plants. When estimating the quality indicators of grain, the methods described and adopted in GOSTs were relied on. There has found that in the variants with pre-sowing treatment of seeds and joint treatment of seeds and plants, it was possible to achieve the maximum manifestation of economic traits. Density of sprouts increased by 11.7–16.3 %, survival rate of plants for harvesting by 8.2–13.6 %, productive tillering by 0.15–0.24, grain content per ear by 4–5 grains, and productivity by 0.43–0.77 t/ha, productivity of the variety ‘Iren’ was 2.82 t/ha, and 2.98 t/ha of the variety ‘Ikar’. Grain productivity was combined with its quality, since protein content was 15.7–16.4 % in the variety ‘Iren’ and 13.7–14.1 % in the variety ‘Ikar’. According to gluten percentage and quality, the grain of the variety ‘Iren’ meets the requirements for strong wheat, while the variety ‘Ikar’ meets the requirements for ordinary wheat. The grain profitability in the experimental variants was 52.3–63.1 % for the variety ‘Iren’ and 47.5–60.6 % for the variety ‘Ikar’, while for the control variety it was 31.4 % and 25.1 %, respectively.